Introduction to population genetics 1: single locus - Balding, David; Morris, Andrew (Henry Stewart Talks, 2004)
Concepts in population genetics, Wright-Fisher model, Drift, Effective population size, Mutation-drift equilibrium, Population structure, Selection, Hardy-Weinberg equilibrium, Coalescent theory
Archived at 2021/02/25